2005
DOI: 10.1007/s10384-004-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Interexaminer Differences in the Traction Test of the Superior Oblique Tendon

Abstract: We demonstrated that the interexaminer differences in the interpretations of the traction test were acceptable, and that after the noninformed examiners had performed the test several times, their interpretations became closer to those of examiner A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A prospective study of SO traction testing showed only fair agreement by masked examiners, little correlation between observed SO laxity and diagnosed SO palsy, and frequent observation of SO laxity in clinical situations where SO palsy was not a consideration. 35 There should be little controversy about considering subjects with MRI evidence of SO atrophy to have true SO palsy. Extrapolating from the sample in this study, perhaps half (10/ 22) of subjects with clinical examinations consistent with SO palsy would not exhibit MRI evidence of SO atrophy or reduced SO contractility.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of SO traction testing showed only fair agreement by masked examiners, little correlation between observed SO laxity and diagnosed SO palsy, and frequent observation of SO laxity in clinical situations where SO palsy was not a consideration. 35 There should be little controversy about considering subjects with MRI evidence of SO atrophy to have true SO palsy. Extrapolating from the sample in this study, perhaps half (10/ 22) of subjects with clinical examinations consistent with SO palsy would not exhibit MRI evidence of SO atrophy or reduced SO contractility.…”
Section: Discussionmentioning
confidence: 99%